2023
DOI: 10.3390/v15020423
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiling of EBV Gene Expression and Promoter Methylation Reveals Latency II Viral Infection and Sporadic Abortive Lytic Activation in Peripheral T-Cell Lymphomas

Abstract: Epstein-Barr virus (EBV) latency patterns are well defined in EBV-associated epithelial, NK/T-cell, and B-cell malignancies, with links between latency stage and tumorigenesis deciphered in various studies. In vitro studies suggest that the oncogenic activity of EBV in T-cells might be somewhat different from that in EBV-tropic B lymphoid cells, prompting us to study this much less investigated viral gene expression pattern and its regulation in nine EBV+ peripheral T-cell lymphoma (PTCL) biopsies. Using froze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…In consonance, EBV-infected T cells demonstrate in vitro a potential oncogenic distinct from those observed in LCLs, including different viral gene expression profile ( 111 ). Furthermore, previous studies in vitro demonstrated that T cells are possibly more permissive for the expression of immediate early viral genes than EBV-infected B cells ( 112 , 113 ), with some evidence of this in EBV-associated neoplasia of T cell origin ( 114 ).…”
Section: A Possible Role Of Ebv In the Oncogenesis Of Enktcl And Nktclmentioning
confidence: 99%
See 4 more Smart Citations
“…In consonance, EBV-infected T cells demonstrate in vitro a potential oncogenic distinct from those observed in LCLs, including different viral gene expression profile ( 111 ). Furthermore, previous studies in vitro demonstrated that T cells are possibly more permissive for the expression of immediate early viral genes than EBV-infected B cells ( 112 , 113 ), with some evidence of this in EBV-associated neoplasia of T cell origin ( 114 ).…”
Section: A Possible Role Of Ebv In the Oncogenesis Of Enktcl And Nktclmentioning
confidence: 99%
“…In a small cohort of patients from Hong Kong, it was demonstrated that all cases presented the del30 of LMP1 and the majority of cases carried type 1 EBV ( 114 ). Results like this need to be interpreted with caution.…”
Section: A Possible Role Of Ebv In the Oncogenesis Of Enktcl And Nktclmentioning
confidence: 99%
See 3 more Smart Citations